2021
DOI: 10.3390/ijerph18041521
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing SDL Readiness and Self-Esteem in a Clinical Adult Nursing Practicum after Flipped Learning Education: Comparison of the Contact and Untact Models

Abstract: This study aimed to evaluate the effects of a flipped learning contact model and a flipped learning “untact” model with Korean nursing students undergoing a clinical practicum, and to examine the factors of self-directed learning readiness and self-esteem considering these learning models. The participants included 85 students. Participants were randomly allocated to two models. This study measured self-directed learning readiness, self-esteem, learner motivation, professor–student and clinical instructor–stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In the tool, a higher total sum score indicates a higher degree of self-directed learning readiness. The reliability of this tool has been previously demonstrated by a Cronbach's alpha coefficient ranging from 0.84 to 0.94, and this study showed a Cronbach's alpha of 0.91 (Cho & Kim, 2021;Kim & Yang, 2020).…”
Section: Self-directed Learning Readinesssupporting
confidence: 54%
“…In the tool, a higher total sum score indicates a higher degree of self-directed learning readiness. The reliability of this tool has been previously demonstrated by a Cronbach's alpha coefficient ranging from 0.84 to 0.94, and this study showed a Cronbach's alpha of 0.91 (Cho & Kim, 2021;Kim & Yang, 2020).…”
Section: Self-directed Learning Readinesssupporting
confidence: 54%
“…Wilson et al found that only 5.7% of students preferred the flipped method alone [ 32 ]. Cho and Kim reported that students showed inferior self-directed learning readiness and instructor–student interaction in online flipped learning compared to their counterparts who received face-to-face flipped learning [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the online format of flipped classrooms should be carefully implemented to avoid negative learning outcomes. Cho and Kim reported inferior self-directed learning readiness and professor–student interaction when comparing online to face-to-face flipped learning [ 10 ]; therefore, these parameters should be carefully considered when implementing online flipped classrooms. On the other hand, Smith and Boscak utilized the flipped classroom mode of instruction in restructuring a course to an online format [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study did not attempt to analyze other cofounding factors that could affect students' SDL, such as students' self-esteem, learning motivation, studentteacher interaction and clinical practice stress. 26 Instead, this study only included the study programs (international vs regular program) in the analysis. Another important limitation is that this study only conducted cross-sectionally.…”
Section: " Even In the Class When I Don't Understand Something That's...mentioning
confidence: 99%